Experimental kinetics studies of seeded batch crystallisation of mono-ammonium phosphate - Utomo, Johan; Maynard, Nicoleta; Asakuma, Y.; Maeda, K.; Fukui, K.; Tade, Moses (Elsevier, 2010)
A seeded batch cooling crystalliser in a laboratory setup was utilised to produce mono-ammonium phosphate (NH4H2PO4) crystals. The effects of different initial saturation, seed size and seed loading ratio on crystal size distribution were thoroughly studied to gather more insight into mono-ammonium phosphate batch crystallization, its kinetics, and for model validation purposes. The seed loading ratio shows the most significant effect on the crystal size distribution profiles followed by the supersaturation factor and seed size. The supersaturation level not only influences the growth rate but the crystal shape as well. A simultaneous method has been applied in the procedure for the estimation of crystallisation kinetics. The nucleation constant (kb) was found to be in the range of 1.0–6.9 × 108 [no/kg s (kg/kg)b+1] and the growth constant (kg) measured was in the range of 3.0–9.4 × 10−5 [m/s (kg/kg)g] with the nucleation (b) and growth (g) exponents determined as 2.2 and 1.4, respectively. Wavelet orthogonal collocation method was utilised to solve the seeded batch crystalliser model and the solution was compared with the experimental data.